Ribka Tjiptaning's Provocative Speaking Action in Social Media: Forensic Linguistic Study - Sarifuddin Kamaruddin; Tadjuddin Maknun; Ery Iswary (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Buton, 2021)
This study aims to: (1) explain the lingual form of inciting Ribka Tjiptaning on social media and (2) explain the meaning of denotation and the incitement connotation of Ribka Tjiptaning on social media. The data in this study are language that contains the crime of incitement by Ribka Tjiptaning on the social media YouTube. While the source of data in this study is the social media youtube. The method used in this research is descriptive with qualitative approach, data collection techniques in the form of look-see and take notes. Data were analyzed using qualitative content analysis (qualitative content analysis). The results of this study indicate that: the data containing denotative and connotative meanings in Ribka Tjiptaning's utterances on social media YouTube amounted to 7 denotative meanings and 5 connotative meanings. Ribka Tjiptaning's speech contained rejection and accusations that the government was playing with the Covid 19 vaccine. This speech is an act against the law by disseminating information that can provoke / incite.